OR fire virtual training simulator: design and face validity - Dorozhkin, Denis; Olasky, Jaisa; Jones, Daniel B.; Schwaitzberg, Steven D.; Jones, Stephanie B.; Cao, Caroline G. L.; Molina, Marcos; Henriques, Steven; Wang, Jinling; Flinn, Jeff; De, Suvranu (Surgical endoscopy, 2017)
Background The Virtual Electrosurgical Skill Trainer is a tool for training surgeons the safe operation of electrosurgery tools in both open and minimally invasive surgery. This training includes a dedicated team-training module that focuses on operating room (OR) fire prevention and response. The module was developed to allow trainees, practicing surgeons, anesthesiologist, and nurses to interact with a virtual OR environment, which includes anesthesia apparatus, electrosurgical equipment, a virtual patient, and a fire extinguisher. Wearing a head-mounted display, participants must correctly identify the “fire triangle” elements and then successfully contain an OR fire. Within these virtual reality scenarios, trainees learn to react appropriately to the simulated emergency. A study targeted at establishing the face validity of the virtual OR fire simulator was undertaken at the 2015 Society of American Gastrointestinal and Endoscopic Surgeons conference. Methods Forty-nine subjects with varying experience participated in this Institutional Review Board-approved study. The subjects were asked to complete the OR fire training/prevention sequence in the VEST simulator. Subjects were then asked to answer a subjective preference questionnaire consisting of sixteen questions, focused on the usefulness and fidelity of the simulator. Results On a 5-point scale, 12 of 13 questions were rated at a mean of 3 or greater (92%). Five questions were rated above 4 (38%), particularly those focusing on the simulator effectiveness and its usefulness in OR fire safety training. A total of 33 of the 49 participants (67%) chose the virtual OR fire trainer over the traditional training methods such as a textbook or an animal model. Conclusions Training for OR fire emergencies in fully immersive VR environments, such as the VEST trainer, may be the ideal training modality. The face validity of the OR fire training module of the VEST simulator was successfully established on many aspects of the simulation.